Design of Novel Efficient Multiplexer Architecture for Quantum-dot Cellular Automata - Hamid Rashidi; Abdalhossein Rezai (Журнал нано- та електронної фізики)
One of the promising emerging technology at nanoscale level to replace the conventional CMOS technology is Quantum-dot Cellular Automata (QCA). It has several advantages compared to conventional CMOS technology. Whereas multiplexers play a vital role in digital circuit implementations, this paper presents and evaluates a modular design methodology to build the high-performance 2n:1 multiplexer. An efficient 2:1 QCA multiplexer architecture is proposed as the basic logic unit, which is utilized to present new and efficient 4:1, and 8:1 QCA multiplexer architectures. The proposed architectures have been implemented on the QCADesigner version 2.0.1. Our implementation results show that the proposed QCA multiplexer architectures have the best performance compared to other multiplexer architectures and outperform most of them in terms of area and clock zones.